COVID 19: Are Our Green Areas Enough for People’s Well-being (International Journal of Built Environment and Sustainability, 2022)
Malaysians’ overall well-being, particularly in urban areas, has been seriously affected physically and emotionally due to the series of imposed lockdowns in the country. The number of mental health problems such as depression, anxiety, and loneliness has increased tremendously during the lockdown period. Various studies suggest that these mental health issues could be coped with if people are allowed to access urban greeneries and public green spaces during the pandemic. However, the degree to how adequate existing green areas are to fulfil an urban community’s needs with strict social distancing compliance is still vaguely interpreted in the literature. It is still arguable that the current 10 per cent green area requirement is still relevant to the current context of the COVID-19 pandemic. This study aims to determine the sufficient amount of green areas for people’s well-being during the pandemic, based on the local population, accessibility to green areas, and compliance with the new norm of social distancing by a minimum of one meter. Therefore, an urban neighbourhood in Iskandar Puteri, Johor, Malaysia was selected and simulated using GIS spatial analysis based on the highlighted parameters. As a result, the study found that the current size of existing green areas in the neighbourhood is insufficient in terms of compliance with the parameters, especially Malaysia’s social distancing requirements. This study could provide a platform for future planning to include pandemic risk reduction into urban planning policies, especially in the context of Malaysia, to cater to future uncertainties
Keywords: Well- being, neighbourhood’s green areas, GIS spatial analysis, green space’s policy